Comparison of the financial performance of Iraqi commercial banks contributing before and after ISIS: An Analytical study of a sample of private Iraqi commercial banks - Yasir, Mohanad Hameed; Obaid, Hayder Jasim; Atiyah, Sajjad Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Many countries have recently been exposed to terrorist operations. However, Iraq was one of the most affected by those operations which carried out by the ISIS terrorist organization. This reflected negatively on all aspects of life, including the financial sector and specifically Iraqi banks of all its kinds, which negatively reflected on the performance of many banks. For the purpose of diagnosing the performance of some banks in the period following the ISIS occupation of parts of Iraq in (2014), our study attempted to recognize the performance of some commercial banks in the previous period and during the terrorist occupation of parts of Iraq and diagnose the time series to take into account in the future researches. To this end, we used the data of (11) Iraqi commercial banks for the period (2011-2016). the purpose of the research, the period was divided into two time series. First one from (2011-2013), the period which preceding the ISIS terrorist operations. The second time series from (2014-2016), The period in which the ISIS terrorist operations were prevalent. We relied in the analysis on some of the banking performance indicators, and concluded to many results. One of them that the Iraqi banking sector in general has been negatively affected by the ISIS terrorist operations, which was clearly reflected in the return on assets, the return on equity and the net interest margin, as well as increased borrowing by the banking sector to face obligations for Immediate withdrawal of deposits.